Effect of Blue Finance and Marine Environmental Quality on the Marine Fishery Economy - Yiying Jiang; Lei Huang; Xiya Zhu; Weirong Song; Yang Liu (Fishes)
This study investigates the effects of blue finance and marine environmental quality of the marine fishery economy using panel data for marine fisheries in China’s coastal provinces spanning 2011–2023. We use entropy, moderating effects, and threshold effects to calculate the level of blue finance and marine environmental quality, the moderating role of marine environmental quality in blue finance’s effect on the marine fishery economy, and the threshold effect of blue finance and marine environmental quality on the marine fishery economy. We find that (1) blue finance can improve the marine fishery economy, with an influence coefficient of 0.245. (2) The quality of marine environment plays a transmission mechanism role in the impact of blue finance on the development of marine fishery economy quality. (3) Blue finance and marine environmental quality both have a first-order threshold effect on the marine fishery economy, showing a U-shaped curve relationship.